2010
DOI: 10.1364/ol.35.003150
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sensor based on metallic photonic crystal slabs

Abstract: We present a hydrogen sensor based on metallic photonic crystal slabs. Tungsten trioxide (WO(3)) is used as a waveguide layer below an array of gold nanowires. Hydrogen exposure influences the optical properties of this photonic crystal arrangement by gasochromic mechanisms, where the photonic crystal geometry leads to sharp spectral resonances. Measurements reveal a change of the transmission depending on the hydrogen concentration. Theoretical limits for the detection range and sensitivity of this approach a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 14 publications
0
31
0
2
Order By: Relevance
“…So they neither generate sparks nor rely on heat exchange and have no risk of gas ignition. With the development of optoelectronic technology and micromachining technology, more and more new work such as sensors based on fiber grating [6], [7], evanescent field [8], [9], metallic photonic crystal structures [10] and surface plasmon Manuscript resonance [11]- [13] are springing up. However, some of them have an all-fiber sensing system but a low sensitivity, while some others own a high sensitivity but introducing bulk-optic components which may introduce instability to optical system.…”
Section: Introductionmentioning
confidence: 99%
“…So they neither generate sparks nor rely on heat exchange and have no risk of gas ignition. With the development of optoelectronic technology and micromachining technology, more and more new work such as sensors based on fiber grating [6], [7], evanescent field [8], [9], metallic photonic crystal structures [10] and surface plasmon Manuscript resonance [11]- [13] are springing up. However, some of them have an all-fiber sensing system but a low sensitivity, while some others own a high sensitivity but introducing bulk-optic components which may introduce instability to optical system.…”
Section: Introductionmentioning
confidence: 99%
“…In this emergent hydrogen economy [1], the reliable and sensitive detection of hydrogen is crucial to ensure the safety of industrial workers and consumers alike [2]. One possible solution to fulfill these requirements is an optical hydrogen sensor based on plasmonic palladium nanostructures [3][4][5]. The optical excitation and readout minimizes the risk of self-ignition, while the plasmonic palladium structures provide a highly sensitive and hydrogen-specific detection method.…”
Section: Introductionmentioning
confidence: 99%
“…Sensitive material such as Pd alloys, Pd nanoparticles oxide materials ðWO 3 ; Pd 2 VO 5 Þ, or Mg alloys with a cap layer of Pd could be envisioned. For example, Nau et al reported that hydrogen sensor is implemented with the change of optical properties of waveguide layer by gasochromic mechanisms [23] and tungsten trioxide ðWO 3 Þ is used as a waveguide layer below a thin metal grating. Our designed structure is also expected to work as a sensitive hydrogen sensor by substituting dielectric layer for tungsten trioxide.…”
Section: Resultsmentioning
confidence: 99%